Total Quality Management (TQM): Decision Making Process Model at Planning Phase for Housing Development in Malaysia - Nurul Atiqah Mohd Sofberi; Rozlin Zainal; Md Fauzi Ahmad (International Journal of Supply Chain Management, 2018)
The main aim of this study is to develop a process model for decision making in the planning phase of housing development in Malaysia. This paper identifies the decision making practiced among Malaysian housing developers at planning phase and examines the three main parts in making decisions which are methods, tools, and information. The paper then investigates whether the three main parts (methods, tools, and information) are strongly related to the decision making process. This paper involves the development of a theoretical model by integrates the models developed by numerous authors and researchers on the subject of decision making. The descriptive statistical technique is conducted and the regression analysis is organize using Structural Equation Modelling (SEM) with AMOS to see the relationship between the three main parts (methods, tools, and information) in making the decision. Thus, this paper is beneficial as a guide for housing developers and governments in making a decision at planning phase for housing development.